2019
DOI: 10.6028/nist.tn.2041
|View full text |Cite
|
Sign up to set email alerts
|

Towards a process to quantify the hazard of fire protection design alternatives

Abstract: There are a variety of new, improved, and/or innovative fire protection technologies that have the potential to improve fire protection and life safety in residences including barrier fabrics for upholstered furniture, new nano-scaled flame retardants, and better fire detection technology. However, there is no accepted methodology available to determine the absolute or even relative performance of different technologies. The Engineering Laboratory of the National Institute for Standards and Technology (NIST) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The association is likely the person being intimate with the fire in many cases. In general, though, the deadliness of a fire is correlated with its size [12], while recent research [11] suggests that most injury-inducing fires are not reported to the fire department, which in turn suggests that most injuries occur in relatively small fires.…”
Section: Peoplementioning
confidence: 99%
See 3 more Smart Citations
“…The association is likely the person being intimate with the fire in many cases. In general, though, the deadliness of a fire is correlated with its size [12], while recent research [11] suggests that most injury-inducing fires are not reported to the fire department, which in turn suggests that most injuries occur in relatively small fires.…”
Section: Peoplementioning
confidence: 99%
“…In particular, a fire's growth is in part determined by the behavior of the people around it rather than being independent of the people around it. Fires during the early morning hours are more deadly than at other times [12]. That is likely due to an increased time to react to fire cues thus allowing the fire to grow further before people react.…”
Section: Firementioning
confidence: 99%
See 2 more Smart Citations
“…What is still largely lacking are the tools to make the process tenable. To that end, the Fire Research Division at the National Institute of Standards and Technology (NIST) has been exploring the process [13,14,15,16] in order to develop tools that will make Monte Carlo fire hazard analysis a more widely used form of analysis using the Consolidated Fire And Smoke Transport (CFAST) model. The result of this effort is the CFAST Fire Data Generator (CData), documented in this report.…”
Section: Getting Startedmentioning
confidence: 99%